Complete pentalogy of Cantrell associated with exencephaly: a rare case report - Rajasekaran, Anandraj; Ekanath, Latha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Complete pentalogy of Cantrell (PC) is a rare condition with an incidence of 1 in 100000 pregnancies. The spectrum includes defects in the diaphragm, anterior abdominal wall, diaphragmatic pericardium, lower sternum and congenital cardiac anomalies. We hereby report a case of complete pentalogy of Cantrell associated with exencephaly.